A proposed institutional five-year development plan for Olivarez College, Paranaque - Olivarez, Eric de Leon (Animo Repository, 1995)
This study proposes an institutional five-year development plan for Olivarez College. The proposed plan covers the three major academic departments of the school namely: Elementary, High School, and College. The rationale for the institutional planning cannot be over-emphasized as every organization needs to undergo a change process so that it can develop and ensure its continual existence and growth. The study's theoretical framework was influenced by the planning process model of Bower and Soriano which consists of: environmental analysis, resource analysis, and value analysis. The researcher reviewed various materials and literature regarding institutional planning: the processes involved, the approaches, and the available models. The author also looked at development plans of other educational institutions to get a clearer perspective of how these schools conduct their own planning programs. Using the descriptive method and documentary analysis as framework of the study's design and methodology, the researcher made use of special instruments to gather input for the environmental, resource and value analyses. Respondents were parents, faculty members, key administrative officers, and students. The study revealed that the municipality of Paranaque is undergoing rapid development as evidenced by booming commercial establishments, urban housing programs and industrial sites. Majority of Olivarez College clients come from above-average income bracket and mostly residents of the municipality. The PAASCU/PACU-COA self-surveys revealed that the school is on the right track in the pursuit of academic excellence and quality service. Inputs from parents, students, teachers and administrators were gathered as to their expectations and their perceptions as to the extent to which these goals are being carried out by the school. The expectations of parents were similar to the goals of the school and these were perceived to be widely carried out. The study concluded that Olivarez College can establish linkages with its environment and clientele for its development programs. The self surveys revealed that the school is on the right track vis-a-vis its mission-vision. The following areas should be inclusive in the proposed development plan: faculty, instruction, laboratory, library, physical plant, student services, and community outreach. The evident weaknesses can be remedied in the proposed development plan. Recommendations included an establishment of a Planning Committee to serve as clearing house of departmental plans and to set the directions for the institutional plans. All weak areas identified in the self-surveys should be immediately addressed. The Institutional Five-Year Development Plan should be fully sustained and carried out for the benefit of the school, in general and the students, in particular.